Analisis Praktik Bisnis Ditinjau Dari Etika Bisnis Islam (Studi Pada PT. Bandung Eco Sinergi Teknologi) - Khoerunisa, Firda; Midisen, Kisanda; Mamun, Sukron; Ainulyaqin, MH (ITB AAS INDONESIA Surakarta, 2024)
This research aims to analyze business practices in terms of Islamic business ethics (Study at PT. Bandung Eco Sinergy Teknologi). This research uses non-statistical qualitative descriptive research methods. The data collection methods used were interviews, observation, documentation and literature study. The data obtained is then analyzed qualitatively, selecting what is important and what will be studied, describing it into words and sentences, then reducing the data, presenting the data and finally drawing conclusions. Based on the research methods and materials collected from this study, it was concluded that Business Practice Analysis, as carried out at PT. Bandung Eco Synergy Technology is viewed from Islamic Business Ethics, namely using a sharia-level direct sales system or PLBS. This is permitted, but on condition that it does not contain elements of pyramid schemes, fund raising, gharar, usury and maysir. And there are several types of contracts including sale and purchase contracts, wakalah contracts, and ju'Ã¢lah contracts which are not mutually binding. Next, related to the Analysis of PT Business Practices. Bandung Eco Sinergi Teknologi explains that the